Social media and mountain visits – is this ‘friendship’ sustainable? - Cholakova, Siya; Dogramadjieva , Elka (Turyzm/Tourism, 2025)
The role of social media in tourism has already been acknowledged in the academic literature but still little is known about its specific influence on mountain tourism in the context of the growing popularity of outdoor activities that threaten to harm fragile areas. The aim of this article is to find out the effect of social media on such visits, to outline patterns of tourist behaviour, as well as to reveal social media–induced effects, both negative and positive, regarding the sustainability of mountain tourism. Using an online survey among the members of a Bulgarian mountaineering Facebook group, we found out that it was information of practical use that was mostly searched for by its members, and which in turn can be easily converted into real visits to the area, and as such mainly attracting novice mountaineers. The study uncovered purely pragmatic perceptions in terms of sharing information and pictures about places in the mountains, with limited awareness about the possible negative environmental effects from the overpopularisation of these areas. This could be classified as a consumerist attitude towards the mountains that is nurtured by social media. On the positive side, such unawareness can be tackled by social media due to its mass informative power.